Celastrol nanoparticles inhibit corneal neovascularization induced by suturing in rats - Li ZR (Dove Medical Press, 2012)
Zhanrong Li1, Lin Yao1, Jingguo Li2, Wenxin Zhang1, Xianghua Wu1, Yi Liu1, Miaoli Lin1, Wenru Su1, Yongping Li1, Dan Liang11State Key Laboratory of Ophthalmology, Zhongshan Ophthalmic Center, Sun Yat-Sen University, 2School of Chemistry and Chemical Engineering, Sun Yat-Sen University, Guangzhou, People's Republic of ChinaPurpose: Celastrol, a traditional Chinese medicine, is widely used in anti-inflammation and anti-angiogenesis research. However, the poor water solubility of celastrol restricts its further application. This paper aims to study the effect of celastrol nanoparticles (CNPs) on corneal neovascularization (CNV) and determine the possible mechanism.Methods: To improve the hydrophilicity of celastrol, celastrol-loaded poly(ethylene glycol)-block-poly(ε-caprolactone) nanopolymeric micelles were developed. The characterization of CNPs was measured by dynamic light scattering and transmission electron microscopy analysis. Celastrol loading content and release were assessed by ultraviolet-visible analysis and high performance liquid chromatography, respectively. In vitro, human umbilical vein endothelial cell proliferation and capillary-like tube formation were assayed. In vivo, suture-induced CNV was chosen to evaluate the effect of CNPs on CNV in rats. Immunohistochemistry for CD68 assessed the macrophage infiltration of the cornea on day 6 after surgery. Real-time quantitative reverse transcription-polymerase chain reaction and enzyme-linked immunosorbent assay were used to evaluate the messenger ribonucleic acid and protein levels, respectively, of vascular endothelial growth factor, matrix metalloproteinase 9, and monocyte chemoattractant protein 1 in the cornea.Results: The mean diameter of CNPs with spherical shape was 48 nm. The celastrol loading content was 7.36%. The release behavior of CNPs in buffered solution (pH 7.4) showed a typical two-phase release profile. CNPs inhibited the proliferation of human umbilical vein endothelial cells in a dose-independent manner and suppressed the capillary structure formation. After treatment with CNPs, the length and area of CNV reduced from 1.16 ± 0.18 mm to 0.49 ± 0.12 mm and from 7.71 ± 0.94 mm2 to 2.29 ± 0.61 mm2, respectively. Macrophage infiltration decreased significantly in the CNP-treated corneas. CNPs reduced the expression of vascular endothelial growth factor, matrix metalloproteinase 9, and monocyte chemoattractant protein 1 in the cornea on day 6 after suturing.Conclusion: CNPs significantly inhibited suture-induced CNV by suppressing macrophage infiltration and the expression of vascular endothelial growth factor and matrix metalloproteinase 9 in the rat cornea.Keywords: celastrol, PEG-b-PCL nanopolymeric micelles, corneal neovascularization, macrophages, VEGF, MMP-9